Question
upstudy study bank question image url

Find each derivative 3) \( y=\left(\frac{x}{3 x^{2}+2 x+1}\right)^{\frac{1}{3}} \)

Ask by Barber Mullins. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( y = \left(\frac{x}{3x^{2}+2x+1}\right)^{\frac{1}{3}} \) is: \[ \frac{dy}{dx} = \frac{1 - 3x^{2}}{3x^{\frac{2}{3}}(3x^{2} + 2x + 1)^{\frac{4}{3}}} \]

Solution

We wish to differentiate   y = [x/(3x² + 2x + 1)]^(1/3). Step 1. Write y in terms of an inner function. Let   f(x) = x/(3x² + 2x + 1),   so that y = [f(x)]^(1/3). Step 2. Differentiate using the chain rule. The derivative of y with respect to x is   dy/dx = (1/3) [f(x)]^(–2/3) · f '(x). Step 3. Compute f '(x) using the quotient rule. Recall the quotient rule: if f(x) = u(x)/v(x), then   f '(x) = (u'v – uv') / [v(x)]². For our function,   u(x) = x → u' = 1,   v(x) = 3x² + 2x + 1 → v' = 6x + 2. Thus,   f '(x) = { (1)(3x² + 2x + 1) – x(6x + 2) } / (3x² + 2x + 1)². Simplify the numerator:   3x² + 2x + 1 – 6x² – 2x = –3x² + 1. So,   f '(x) = (–3x² + 1) / (3x² + 2x + 1)². Step 4. Combine the results. Substitute f(x) and f '(x) back into the chain rule formula:   dy/dx = (1/3) · [x/(3x² + 2x + 1)]^(–2/3) · [ (–3x² + 1) / (3x² + 2x + 1)² ]. Notice that the factor [x/(3x²+2x+1)]^(–2/3) can be rewritten as   [x/(3x²+2x+1)]^(–2/3) = [ (3x²+2x+1)/x ]^(2/3). Thus we have:   dy/dx = (1/3) · [ (3x²+2x+1)/x ]^(2/3) · [ (–3x² + 1) / (3x²+2x+1)² ]. Step 5. Simplify the expression. Combine the factors involving (3x² + 2x + 1):   [ (3x²+2x+1)^(2/3) ] / (3x²+2x+1)²     = 1 / (3x²+2x+1)^(4/3). Also, the x in the denominator contributes a factor of x^(2/3) from [ (3x²+2x+1)/x ]^(2/3). Thus, the derivative becomes:   dy/dx = (1/3) · (–3x² + 1) / [ x^(2/3)(3x²+2x+1)^(4/3) ]. It is often nice to write the numerator as (1 – 3x²). So the final derivative is:   dy/dx = (1 – 3x²) / [ 3·x^(2/3)·(3x²+2x+1)^(4/3) ]. This is the desired derivative.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the derivative of \( y=\left(\frac{x}{3 x^{2}+2 x+1}\right)^{\frac{1}{3}} \), we can apply the chain rule and the quotient rule. Let \( u = \frac{x}{3x^2 + 2x + 1} \). The derivative of \( y = u^{\frac{1}{3}} \) is given by: \[ \frac{dy}{dx} = \frac{1}{3} u^{-\frac{2}{3}} \cdot \frac{du}{dx} \] Now, we need to calculate \( \frac{du}{dx} \) using the quotient rule: \[ \frac{du}{dx} = \frac{(3x^2 + 2x + 1)(1) - x(6x + 2)}{(3x^2 + 2x + 1)^2} \] Simplifying the numerator: \[ = (3x^2 + 2x + 1) - (6x^2 + 2x) = 3x^2 + 2x + 1 - 6x^2 - 2x = -3x^2 + 1 \] Thus, we have: \[ \frac{du}{dx} = \frac{-3x^2 + 1}{(3x^2 + 2x + 1)^2} \] Now substituting this back into the derivative of \( y \): \[ \frac{dy}{dx} = \frac{1}{3} u^{-\frac{2}{3}} \cdot \frac{-3x^2 + 1}{(3x^2 + 2x + 1)^2} \] Substituting back \( u \): \[ = \frac{1}{3} \left(\frac{x}{3x^2 + 2x + 1}\right)^{-\frac{2}{3}} \cdot \frac{-3x^2 + 1}{(3x^2 + 2x + 1)^2} \] Finally, we can express this in a simplified form: \[ \frac{dy}{dx} = \frac{1}{3} \left(\frac{3x^2 + 2x + 1}{x}\right)^{\frac{2}{3}} \cdot \frac{-3x^2 + 1}{(3x^2 + 2x + 1)^2} \] And that gives us the derivative \( \frac{dy}{dx} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy